Startegi Komunikasi Oraganisasi Forum Mahasiswa Karanganyar dalam Mempertahankan Eksistensi Melalui Event Eksternal Di Kabupaten Karanganyar: Startegi Komunikasi Oraganisasi Forum Mahasiswa Karanganyar dalam Mempertahankan Eksistensi Melalui Event Eksternal Di Kabupaten Karanganyar - Hermawanti, Faizah; Hindra, Nurnawati; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The purpose of this research is to look at the Organizational Communication Strategy of the Karanganyar Student Forum in Maintaining Existence through External Events in Karanganyar Regency. This study uses the theory of organizational communication strategy. This research uses a qualitative descriptive approach. Data collection techniques in this study were using participant observation methods, in-depth interviews and documentation. Data analysis techniques use data collection, data reduction, presenting data and drawing conclusions or verification. Based on the research results, it was found that determining the audience of an external Expo Campus event conducted by Formaka to maintain its existence, that is seen from the initial purpose of holding the Expo Campus, namely to introduce and disseminate information about lectures to Senior High School and Vocational School students who are still in school so that motivate them to continue their education to a higher level. The message was structured so that many would come to the Expo Campus in the form of outreach activities to Senior High School and Vocational School schools in Karanganyar, then making unique and interesting pamphlets and finally doing branding on social media. The method used to maintain the existence of Formaka is the Expo Campus. The selection and use of the media most often used by Formaka in conveying messages is Instagram, in collaboration with mass media such as radio. The conclusion from this study is that the organizational communication strategy of the Karanganyar student forum in maintaining its existence through external events in Karanganyar Regency, namely using the Expo Campus, can be said to be successful. Keywords: Organizational Communication Strategy, Formaka, Existence, External Event.